Global stagflation - Jongrim Ha; M. Ayhan Kose; Franziska Ohnsorge (Koç University-TÜSIAD Economic Research Forum (ERF), 2022)
Global inflation has risen sharply from its lows in mid-2020, on rebounding global demand, supply bottlenecks, and soaring food and energy prices, especially since the Russian Federation's invasion of Ukraine. Markets expect inflation to peak in mid-2022 and then decline, but to remain elevated even after these shocks subside and monetary policies are tightened further. Global growth has been moving in the opposite direction: it has declined sharply since the beginning of the year and, for the remainder of this decade, is expected to remain below the average of the 2010s. In light of these developments, the risk of stagflation-a combination of high inflation and sluggish growth-has risen. The recovery from the stagflation of the 1970s required steep increases in interest rates by major advanced-economy central banks to quell inflation, which triggered a global recession and a string of financial crises in emerging market and developing economies. If current stagflationary pressures intensify, they would likely face severe challenges again because of their less well-anchored inflation expectations, elevated financial vulnerabilities, and weakening growth fundamentals.
Keywords: E31; E32; E52; Q43; 330; Inflation; growth; COVID-19; global recession; monetary policy; fiscal policy; disinflation